Writing a high impact research paper - Maleque, Md. Abdul (2017)
This presentation article shows a systematic journey to write a high impact research paper. First thing that need is the creation of an outline before start working on research paper. Once already decided what topic will be writing about, the next thing should pay attention to is the scope of paper or what will be included in the discussion. The broader the topic is, the more difficult it is to discuss the topic in full details. Basically, the outline will constitute four main parts namely Introduction, Methods, Results and Discussion/Conclusion (IMRaD). It is also necessary to make sure that the paper is complete, consult with other researchers for specific parts to be improved or included.